Comparison of modified mallampati test between sitting and supine positions for prediction of difficult intubation - Khatiwada, S; Bhattarai, B; Pokharel, K; Acharya, R; Ghirnire, A; Baral, DD (Health Renaissance, 2012)
Background: Modified Mallampati test is a standard method of assessing the airway for predicting potentially difficult laryngoscopy and intubation. This test requires the patient to be in sitting position for airway evaluation. Although applicable to the majority of patients, airway evaluation in sitting position may not always be convenient or advisable. Objectives: To compare modified Mallampati grades between sitting and supine position and to find out their corelation to Cormack and Lehane laryngoscopy grade. Materials: This prospective study was conducted in 215, ASA I and II patients undergoing various routine surgical procedures under general anaesthesia, in BPKIHS, Dharan over a period of 3 months. The airway assessment was done using modified Mallampati grade in sitting and supine positions. Mallampati grade of III or IV was defined as the predictor of difficult airway. The laryngoscopy grade was assessed using the Cormack and Lehane grading scale. Grade III or IV of Cormack and Lehane grades was defined as the difficult laryngoscopy and assumed as the predictor of difficult intubation. Statistical measures including sensitivity, specificity, positive and negative predictive values and accuracy were used for comparing the two positions for predicting difficult or ease of intubation. Results: Out of 215 patients, majority 146(68%) were females. Mallampati grade III or IV was observed in more patients in supine position compared to sitting position (48.3% vs. 35.8%, p = 0.008). Difficult laryngoscopy was observed in 13(6%) patients. Sensitivity of modified Mallampati test was 77% in both the positions. Predictive value of Mallampati grading for difficult intubation were 13% and 10% and for easy intubation were 96% and 97% respectively in sitting and supine position. Specificity and accuracy of modified Mallampati test were both 67% in sitting position, where as they were 54% and 55% respectively in supine position. Conclusion: Modified Mallampati grade significantly worsens in supine position compared to sitting. However, airway evaluation in both the positions almost equally predicts for difficult intubation. DOI: http://dx.doi.org/10.3126/hren.v10i1.6000 HREN 2012; 10(1): 12-15